2009
DOI: 10.3354/meps08206
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates of juvenile green turtles Chelonia mydas from three ecologically distinct foraging habitats along the east central coast of Florida, USA

Abstract: A generalized additive mixed modeling approach was used to assess somatic growth for juvenile green turtles Chelonia mydas at 4 sites in 3 ecologically distinct foraging habitats along the east central coast of Florida, USA. The 3 habitats were a man-made nuclear submarine turning basin (Trident Submarine Basin), an estuary (Indian River Lagoon), and oceanic sabellariid worm rock reefs (Sebastian Inlet and St. Lucie Power Plant). Turtles from the Indian River Lagoon site grew significantly faster than turtles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 26 publications
1
61
0
1
Order By: Relevance
“…Since recapture rates of turtles are highly variable (Piovano et al 2011), using just 1−2 yr of growth provides an incomplete life history and is likely to miss rare growth spurts. Therefore, long-term datasets are more accurate in estimating life-stage durations as they are more likely to capture the variability in and full distribution of growth rates, but such studies are quite laborious and time-consuming, requiring multiple recaptures of animals (Bjorndal et al 2000, Balazs & Chaloupka 2004b, Kubis et al 2009, Eguchi et al 2012, Avens & Snover 2013, Sampson et al 2015, Goshe et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Since recapture rates of turtles are highly variable (Piovano et al 2011), using just 1−2 yr of growth provides an incomplete life history and is likely to miss rare growth spurts. Therefore, long-term datasets are more accurate in estimating life-stage durations as they are more likely to capture the variability in and full distribution of growth rates, but such studies are quite laborious and time-consuming, requiring multiple recaptures of animals (Bjorndal et al 2000, Balazs & Chaloupka 2004b, Kubis et al 2009, Eguchi et al 2012, Avens & Snover 2013, Sampson et al 2015, Goshe et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…This longer duration at vulnerable sizes could decrease the probability of older values of AgeSM resulting from slow length growth or larger values of size at maturity from slow mass growth. In contrast, density-dependent effects could yield older AgeSM and smaller LengthSM and MassSM, as populations recover , Chaloupka et al 2008) and somatic growth rates slow (Bjorndal et al 2000, Balazs & Chaloupka 2004, Kubis et al 2009). In addition, sea turtles are subjected to a large number of threats (Lutcavage et al 1997, Bolten et al 2011), many of which produce sublethal effects that can decrease juvenile growth rates (McCauley & Bjorndal 1999, Roark et al 2009) and thus could result in older values of AgeSM and smaller size at maturity.…”
Section: Comparisons With Wild Populationsmentioning
confidence: 99%
“…Somatic growth rates in sea turtles vary spatially and temporally (Diez & van Dam 2002, Balazs & Chaloupka 2004, Kubis et al 2009, Bjorndal et al 2013b However, variation in age and size of wild turtles could be decreased -although not below the level of variation in CTF turtles -by increased mortality of slow-growing turtles that remain in vulnerable size classes for a longer time. This longer duration at vulnerable sizes could decrease the probability of older values of AgeSM resulting from slow length growth or larger values of size at maturity from slow mass growth.…”
Section: Comparisons With Wild Populationsmentioning
confidence: 99%
“…At a local scale, previous studies have found foraging site specific growth rates, likely as a consequence of habitat quality and availability of food resources (Balazs & Chaloupka 2004, Kubis et al 2009). The differences observed here between foraging aggregations are also likely attributable to habitat rather than to genetic stock or to size distributions, as neither of these aspects differ significantly among sites.…”
Section: Foraging Site Specific Growth and Abundance Trendsmentioning
confidence: 99%
“…Spatial and temporal variability in somatic growth dynamics, particularly when coupled with abundance estimates, make good indicators of the quality of foraging sites, as lower growth rates may imply less food availability (Balazs & Chaloupka 2004, Kubis et al 2009, and declines in somatic growth rates coupled with higher abundance suggest a density-dependent effect (Bjorndal et al 2000a, Kubis et al 2009). …”
Section: Introductionmentioning
confidence: 99%